2022
DOI: 10.1097/ijg.0000000000002123
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Access and Utilization Among Glaucoma Patients in a Nationwide Cohort

Abstract: Précis: Despite having lower socioeconomic status on several measures, glaucoma patients do not report more barriers to healthcare access and utilization than non-glaucoma patients.Purpose: To characterize measures of socioeconomic status and barriers to healthcare access and utilization between patients with and without a diagnosis of glaucoma.Methods: Patients aged 65 years and over who enrolled in the NIH All of Us Research Program, a nationwide longitudinal cohort, were extracted. We analyzed demographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…While prior studies have linked eye care access and glaucoma prevalence, this study specifically examines the relationship between eye care access and levels of glaucoma severity, as well as the likelihood of having incisional surgery. 5,6 A possible explanation for the association between access to eye care and increased likelihood of all levels of glaucoma severity is that patients with glaucoma must visit an eye care provider to receive a formal diagnosis. This is in line with a study by Ko et al, 10 which demonstrated that individuals with more health care utilization were more likely to be diagnosed with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While prior studies have linked eye care access and glaucoma prevalence, this study specifically examines the relationship between eye care access and levels of glaucoma severity, as well as the likelihood of having incisional surgery. 5,6 A possible explanation for the association between access to eye care and increased likelihood of all levels of glaucoma severity is that patients with glaucoma must visit an eye care provider to receive a formal diagnosis. This is in line with a study by Ko et al, 10 which demonstrated that individuals with more health care utilization were more likely to be diagnosed with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that individuals with advanced stages of the disease require more procedures and eye care resources and have shorter recommended follow-up times due to the severity of their disease. 5,11 However, those with access to eye care also had increased odds of mild and moderate glaucoma compared with individuals without access to eye care. Our finding of a higher prevalence of any glaucoma in those with access to eye care suggests the possibility of missed glaucoma diagnoses in individuals who are unable to see an eye care provider.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations